Sociology of globalization - Sassen, Saskia (New York, 2007)
Sassen identifies two sets of processes that make up globalization: the first and more commonly studied set of processes is global institutions, from the World Trade Organization to the War Crime Tribunals; the second and less frequently explored set of processes occur at the national and local level, including state monetary policy, small-scale activism that has an explicit or implicit global agenda, and local politics. Emphasizing the interplay between global and local phenomena, Sassen insightfully examines new forms and conditions such as global cities, transnational communities, and commodity chains. This unique approach to globalization offers new interpretive and analytic tools to understand the complexity of global interdependence. Sociology of Globalization is part of the Contemporary Societies series.
Keywords: Globalization - social aspects